Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan - Narwathi, Ni Made Dwi; Putri Trarintya, Mirah Ayu; Putra Astawa, I Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to partially and simultaneously influence the work environment and work motivation on employee job satisfaction at the Guwang Traditional Village LPD. The population in this study were all 32 employees of the Guwang Traditional Village LPD. Determination of the sample using a saturated sample, so that the entire population is used as a sample. After testing the instrument and testing the classical assumptions, then the data was analyzed using multiple linear regression analysis. The results of the analysis show that the work environment has a positive and significant effect on the job satisfaction of LPD employees in the Guwang Traditional Village. Work motivation has a positive and significant effect on job satisfaction of LPD Guwang Traditional Village employees. Work environment and work motivation simultaneously have a positive and significant effect on job satisfaction of LPD Guwang Traditional Village employees. Suggestions that can be put forward in this study are suggested to the Guwang Traditional Village LPD to increase air circulation in the employee’s work space and provide better rewards to employees who are able to show better work performance and increase employee job satisfaction.